The Effect of Class Management on Economic Learning Motivation at SMA Negeri 20 Palembang - Erma Yulaini; Diana Widhi Rachmawati; Devi Nur Ahini Oktavia Putri; Nyoman Tri Chayanti (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2021)
The purpose of this study was to determine the effect of classroom management on motivation to study economics at SMA Negeri 20 Palembang for the 2019/2020 academic year. The research method used quantitative descriptive method. The sample in the research of class X amounted to 54 students. In collecting data the researchers used techniques of documentation and questionnaires. The results showed that the class management had a significant effect on the economic learning motivation received with a large effect from the class management of 31.97%, while the remaining 68.03% was influenced by other factors. Therefore, classroom management is needed in the learning process. Keywords: Classroom Management, Learning Motivation, Management Education